Three sibs with phalangeal anomalies, microcephaly, severe mental retardation, and neurological abnormalities. - Woods, C G (1992)
This paper describes three children of a Pakistani first cousin marriage with a distinctive, non-progressive disorder characterised by variable phalangeal anomalies, microcephaly, pre- and postnatal growth retardation, poor vision, dystonic movements, a characteristic face, and severe mental retardation. This combination of features seems to be distinct and to represent a new autosomal recessive syndrome.